Mysterium Tremendum in a New Key - Hoelter, Mark E. (Zygon, 2021)
In 1917 Rudolf Otto concluded his search for a non-rational grounding for religion—not opposed to science but also not reducible to science. Reflecting on personal experience and engagement with world religions, Otto posited: all religions are rooted in a universal experience. He labeled this experience the mysterium tremendum et fascinosum—an experience so fascinating that one cannot not attend to it, and, at the same time, so humbling and inspiring it also has both awe and terror about it. Now Iain McGilchrist's The Master and His Emissary offers a neurological, “non-rational” grounding for that mysterium. Neuroscientist, Patrick McNamara, and philosopher-theologian, Wesley J. Wildman, expand, refine, and particularize McGilchrist's work. All of this together, besides playing Otto's original mysterium in a new key, holds implications for pro-social intragroup and inter-group work as well as for individual psychotherapeutic and spiritual growth and transformation.